Pengaruh ROE, CR, Dan DER Terhadap Harga Saham Pada Perusahaan Manufaktur (Sub Sektor Food And Beverage) Yang Terdaftar Di BEI Tahun 2017-2021 - Putri Widianti; Diah Yudhawati; Titing Suharti (CV. ITTC INDONESIA, 2023)
This study aims to determine and test the effect of Return On Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER) on Stock Prices in Manufacturing Companies (Food and Beverage Sub Sector) listed on the Indonesia Stock Exchange in 2017 -2021. This study used a sampling method, namely purposive sampling, in order to obtain a sample of 13 companies in the food and beverage sub-sector manufacturing companies listed on the IDX. This research is a quantitative research using secondary data in the form of financial reports obtained from data published by the Indonesia Stock Exchange and yahoo finance. The analysis used in this study is panel data regression analysis, multiple linear regression, classical assumption test by testing the hypothesis F test (simultaneous), t test (partial) and the coefficient of determination (R2). The results of research conducted by panel data regression test showed that the best model used for this study was the Random Effects model. The results of the t test show that the variable Return On Equity (ROE) has a significant effect on stock prices, the Current Ratio (CR) and Debt to Equity Ratio (DER) variables have no effect on stock prices. And the results of the f test show that simultaneously the variables Return On Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER) have a significant effect on stock prices.